Penerapan Metode Role Playing Untuk Meningkatkan Motivasi Belajar Siswa di SMPN 30 Makassar - Sriwahyuni, Ilfa; Raehana, Syarifa; Nengsih, Ratika; Bunyamin, Andi; Syahrul, Muhammad (LP2M Universitas Islam Ahmad Dahlan, 2025)
This study is a Classroom Action Research (CAR) that highlights the effectiveness of the role-playing method in Islamic Religious Education learning in class VIII.8 of SMP Negeri 30 Makassar. The main focus of this study is to improve students' learning motivation. The research sample consisted of 31 students (17 males and 14 females). Data collection was conducted through participant observation and a structured questionnaire consisting of 16 items. The results of the study showed a significant increase in students' learning motivation after the implementation of the role-playing method. The average score of the questionnaire in cycle II (1,921 points, 77.45%) was significantly higher than that in cycle I (1,592 points, 64.19%). This finding shows the effectiveness of the role-playing method in improving students' learning motivation in the context of Islamic Religious Education learning. Further research is recommended to explore the generalization of these findings to other classes and subjects, as well as to identify contextual factors that contribute to improving learning motivation.